Exploring Logical Intuition in Base-Rate Problems Using the Instructional Manipulation Paradigm - Debiao Zhu; Ping Lu; Zhujing Hu; Jianyong Yang; Dandan Nie (Behavioral Sciences)
The default–interventionist model of dual-process theories proposes that stereotype descriptions in base-rate problems are processed using Type 1 processing, while the evaluation of base rates depends on Type 2 processing. The logical intuition view posits that people can process base-rate information using Type 1 processing. This study examined the logical intuition view using the instructional manipulation paradigm. Participants judged the probability that a character in a base-rate problem belonged to a particular group based on either their beliefs or statistics and then rated their confidence in their responses. Results showed that a belief–statistics conflict affected both statistics- and belief-based judgments, resulting in lower probability estimates, longer response times, and lower confidence ratings for conflict items compared to no-conflict items, suggesting participants intuitively processed base rates such that they influenced rapid belief judgments. This intuitive logic effect was observed for extreme base rates, moderate base rates, and moderate base rates with small absolute values. These findings are inconsistent with the default–interventionist model but align with dual-process theories emphasizing logical intuition. The study provides additional evidence for human rationality.